Assessment of the Ground Vulnerability in the Preveza Region (Greece) Using the European Ground Motion Service and Geospatial Data Concerning Critical Infrastructures - Eleftheria Basiou; Ignacio Castro-Melgar; Haralambos Kranis; Andreas Karavias; Efthymios Lekkas; Issaak Parcharidis (Remote Sensing)
The European Ground Motion Service (EGMS) and geospatial data are integrated in this paper to evaluate ground deformation and its effects on critical infrastructures in the Preveza Regional Unit. The EGMS, a new service of the Copernicus Land Monitoring Service, employs information from the C-band Synthetic Aperture Radar (SAR)-equipped Sentinel-1A and Sentinel-1B satellites. This allows for the millimeter-scale measurement of ground motion, which is essential for assessing anthropogenic and natural hazards. The study examines ground displacement from 2018 to 2022 using multi-temporal Synthetic Aperture Radar Interferometry (MTInSAR). The Regional Unit of Preveza was selected for study area. According to the investigation, the area’s East–West Mean Velocity Displacement varies between 22.5 mm/y and −37.7 mm/y, while the Vertical Mean Velocity Displacement ranges from 16 mm/y to −39.3 mm/y. Persistent Scatterers (PSs) and Distributed Scatterers are the sources of these measurements. This research focuses on assessing the impact of ground deformation on 21 school units, 2 health centers, 1 hospital, 4 bridges and 1 dam. The findings provide valuable insights for local authorities and other stakeholders, who will greatly benefit from the information gathered from this study, which will lay the groundwork for wise decision-making and the creation of practical plans to strengthen the resistance of critical infrastructures to ground motion.